Ureakäsitelty puuaines ei kelpaa juurikäävälle - Poteri, Marja (Metsäntutkimuslaitos, 2002)
Selostus artikkelista: Johansson M.S., Pratt J.E. ja Asiegbu, F.O. 2002. Treatment of Norway spruce and Scots pine stumps with urea against the root and butt rot fungus Heterobasidion annosum – possible modes of action. Forest Ecology and Management 157: 87–100.
Julkaisusatoa